The impact of Broad Based Black Economic Empowerment on financial performance of top empowered companies listed on the JSE in South Africa - Govender, Tamara (Research of GSB, 2018)
This dissertation aims to provide insight into the relationship between Broad-Based Black Economic Empowerment (BBBEE) compliance and the financial performance of top empowered companies listed on the Johannesburg Stock Exchange (JSE) in South Africa. This study is similar to two previous studies; the first is on the impact of corporate governance on JSE listed companies for the period 2003 until 2006 and on a sample of 97 JSE listed companies (Abdo & Fisher, 2007). The second is on the contribution of BBBEE on the financial performance on a sample of 49 JSE listed companies from 2005 until 2008 and 2008 until 2010 (van Heerden, 2011). This empirical study was initially on a sample of 100 JSE listed companies from 2009 until 2012 that was derived from JSE listed companies which featured in the annual Financial Mails Top Empowerment Survey Publication from 2009 until 2012. The sample was reduced to 64 units due to delisting, corporate name changes and data unavailability for the period. Corresponding company financial data (share price, price to earnings ratio, price to book value) were obtained for the period 2008 until 2012 from McGgregor BFA database and correlated to BBBEE compliance ratings as published by Financial Mail. JSE indices were obtained from I-Net Bridge. Based on the types of companies, they were grouped into 10 JSE economic sectors such that the performance of each sector could be correlated to the total average BBBEE compliance ratings, financial metrics and JSE indices. For each sample unit, the average BBBEE rating was calculated for the period 2009 until 2012. This was then correlated to the annualised share price return for the same period and to price to earnings ratio and price to book value for 2012. The findings suggest there was a negative and weak relationship between share price and BBBEE compliance rating. There is a positive and weak relationship between price to earnings and price to book value. The cluster of companies with high BBBEE compliance ratings achieved higher and lower annualised share price returns than the respective JSE sector indices. The cluster of companies with low BBBEE compliance ratings also achieved higher and lower annualised share price returns than the respective JSE sector indices. It was also observed that high BBBEE rated companies achieved higher and lower share price returns than low BBBEE rated companies. Companies with high BBBEE compliance ratings achieved both higher and lower price to earnings than the respective JSE indices. Companies with low BBBEE compliance ratings also achieved higher and lower price to earnings than the respective JSE indices. Companies with low and high BBBEE compliance ratings achieved profit to book values below the respective JSE sectors. Of the seven BBBEE compliance indicators five positively correlated to the annualised share price return i.e. employment equity, skills development, preferential procurement, enterprise development and socio- economic development. Ownership, skills development, preferential procurement, enterprise development, socio- economic development positively correlated to the price to earnings ratio. Skills development, preferential procurement, enterprise development, socio- economic development positively correlated to the price to book value ratio.